Elastodynamics Field of Non-Uniformly Moving Dislocation: From 3D to 2D - Shichao Luo; Yinan Cui (Crystals, 2022)
Molecular dynamics (MD) and experiments indicate that the high-speed dislocations dominate the plasticity properties of crystal materials under high strain rate. New physical features arise accompanied with the increase in dislocation speed, such as the “Lorentz contraction” effect of moving screw dislocation, anomalous nucleation, and annihilation in dislocation interaction. The static description of the dislocation is no longer applicable. The elastodynamics fields of non-uniformly moving dislocation are significantly temporal and spatially coupled. The corresponding mathematical formulas of the stress fields of three-dimensional (3D) and two-dimensional (2D) dislocations look quite different. To clarify these differences, we disclose the physical origin of their connections, which is inherently associated with different temporal and spatial decoupling strategies through the 2D and 3D elastodynamics Green tensor. In this work, the fundamental relationship between 2D and 3D dislocation elastodynamics is established, which has enlightening significance for establishing general high-speed dislocation theory, developing a numerical calculation method based on dislocation elastodynamics, and revealing more influences of dislocation on the macroscopic properties of materials.